Molecular Structure, Matrix-Isolation IR Spectrum and UV-Induced Transformations of 2-Amino-5-(4-Methoxyphenyl)-1,3,4-Oxadiazole - Sıdır, Isa; Lopes, Susy; FAUSTO, RUI; Jesus, A. J. Lopes (MDPI, 2025)
The photochemistry of 1,3,4-oxadiazoles remains poorly understood, despite their recognized importance in medicinal chemistry and materials science. In this work, we report a detailed matrix-isolation study of 2-amino-5-(4-methoxyphenyl)-1,3,4-oxadiazole, combining low-temperature infrared spectroscopy with broadband UV photolysis and quantum chemical calculations. Theoretical analysis predicts the gas-phase molecule to exist exclusively as the amino tautomer, populating two nearly isoenergetic conformers (anti and syn) defined by the relative orientation of the amino and methoxy groups. Experimental IR spectra of the compound isolated in Ar and Xe matrices at 15 K confirm sole trapping of the amino tautomer. Annealing of the Xe matrix to the highest achievable temperature induced no detectable spectral changes, consistent with the predicted isoenergetic character of the conformers. Upon broadband UV irradiation (lambda > 200 nm), the compound undergoes ring opening through N-N and C-O bond cleavages, paralleling the behavior of unsubstituted 1,3,4-oxadiazole system. Isocyanates emerge as the predominant photoproducts from these photochemical pathways. Additionally, spectroscopic evidence supports an alternative reaction pathway involving early-stage amino-imino tautomerization, followed by ring-opening of the imino tautomer through isocyanic acid extrusion, leading to the formation of a nitrilimine intermediate. This reactive species subsequently photorearranges into a carbodiimide via a diazirine-mediated pathway. All photoproducts were unambiguously identified through their distinct IR signatures, supported by quantum chemical calculations and reference data from structurally related systems. These findings provide unprecedented insight into the photochemical behavior of substituted 1,3,4-oxadiazoles and unveil new reaction pathways modulated by substituent effects, expanding the understanding of their photoreactivity.
Keywords: Conformers and Tautomers; Matrix-isolation Infrared Spectroscopy; Quantum Chemical Calculations; UV-induced Photochemistry